PHONOLOGICAL COMPETENCE OF CHILDREN WITH DOWN SYNDROME AT SLB C NEGERI 1 YOGYAKARTA - M. Lutfih Baihaqi (Widyariset, 2011)
Down syndrome is the most common chromosome disorder and genetic cause of mental retardation. It occurs because of the presence of an extra copy of chromosome 21. Down syndrome occurs in about one in every 800 live births. Down syndrome occurs with equal frequency across all ethnic groups and subpopulations. This research is intended to acquire a description of phoneme production competence and examines the patterns of deviations which occur as well as identifying the recovering point phonologically of children with down syndrome. The results of the analysis indicate that (1) the deviations in pronunciation occur regularly in each child, for instance, thechange of a certain phoneme occur in other phonemes and it happens repeatedly; (2) The phonological deviations in each child are not the same according to their intelligence, motoric capability, and background environment, (3) The phonological recovery of children with mental retardation requires a certain type of training, but this training will never succeed without supporting and conducive environment.